Development of a market approach to integrate microsources in LV distribution networks - João Paulo Tomé Saraiva (2005)
This paper describes the research under development regarding the integration of several types of micro-source in LV distribution networks. This research is financed through an EU R&D project and tackles several scientific and technological related problems in the fields of micro-source electrical modelling, power system LV operational impact analysis, monitoring and control, power quality and network reliability, protection coordination and personnel safety, communications, economical and electrical market driven procedures and definition of new interconnection standards. In particular, in this paper we describe an approach to schedule micro-source generation and to validate that dispatch from a technical point of view using a lineraized optimization problem. The paper includes results from a case study developed in a LV test network used in the scope of the referred project.